Pengaruh Total Pembiayaan dan Non Performing Financing (NPF) Terhadap Pendapatan Bank Syariah (Studi Bank Pembiayaan Rakyat Syariah di Indonesia Tahun 2015-2018) - Yansyah, Tabri (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
The purpose of this study was to determine the effect of ROA and NPF on UMKM financing at BPRS in Indonesi 2014-2018. This reseach uses quantitative reseach. This study uses secondary data sources. The analisis used is the calssical assumption test and hypothesis testing using the F, t and R2 statistical tests. The results of this study indicate that the Return On Asset (ROA) is know to have a probability value of 0,4611 > 0.05, so that ROA is indicated as having no effect significant toward UMKM financing distribution, while for Non Performing Financing (NPF) it is known that the probability value of 0,0000 <0,05, so that NPF has a positive and significant effect on the distribution of UMKM financing.